Neonatal care practices in sub-Saharan Africa: a systematic review of quantitative and qualitative data - Margaret Bee; Anushree Shiroor; Zelee Hill (BMC, 2018)
Abstract Background Recommended immediate newborn care practices include thermal care (immediate drying and wrapping, skin-to-skin contact after delivery, delayed bathing), hygienic cord care and early initiation of breastfeeding. This paper systematically reviews quantitative and qualitative data from sub-Saharan Africa on the prevalence of key immediate newborn care practices and the factors that influence them. Methods Studies were identified by searching relevant databases and websites, contacting national and international academics and implementers and hand-searching reference lists of included articles. English-language published and unpublished literature reporting primary data from sub-Saharan Africa (published between January 2001 and May 2014) were included if it met the quality criteria. Quantitative prevalence data were extracted and summarized. Qualitative data were synthesized through thematic analysis, with deductive coding used to identify emergent themes within each care practice. A framework approach was used to identify prominent and divergent themes. Results Forty-two studies were included as well as DHS data - only available for early breastfeeding practices from 33 countries. Results found variation in the prevalence of immediate newborn care practices between countries, with the exception of skin-to-skin contact after delivery which was universally low. The importance of keeping newborn babies warm was well recognized, although thermal care practices were sub-optimal. Similar factors influenced practices across countries, including delayed drying and wrapping because the birth attendant focused on the mother; bathing newborns soon after delivery to remove the dirt and blood; negative beliefs about the vernix; applying substances to the cord to make it drop off quickly; and delayed breastfeeding because of a perception of a lack of milk or because the baby needs to sleep after delivery or does not showing signs of hunger. Conclusion The majority of studies included in this review came from five countries (Ethiopia, Ghana, Malawi, Tanzania and Uganda). There is a need for more research from a wider geographical area, more research on newborn care practices at health facilities and standardization in measuring newborn care practices. The findings of this study could inform behaviour change interventions to improve the uptake of immediate newborn care practices.